MODIFICATION OF CARBON DOT STRUCTURE AND CHARACTERISTICS AS PHOTOTHERMAL MATERIALS FOR SOLAR EVAPORATOR APPLICATION - Indriyati
Solar evaporator has been the focus of research in recent decades as an environmentally friendly solutions to the clean water crisis. This technology utilizes abundant solar energy to heat and evaporate water, then condenses the vapor into clean water. However, traditional solar evaporators have low efficiency (<20%) due to the low light absorption of water as well as the complex and expensive infrastructure. One strategy to improve evaporation efficiency is to employ excellent photothermal materials, which can absorb light and convert it into heat. Among various photothermal materials, carbon dots are promising candidates due to their low thermal conductivity, good absorbance and photothermal capabilities, non-toxicity, and ease of synthesis and functionalization. However, the absorbance peak of carbon dots is mainly in the ultraviolet region, necessiting functionalization or structural modification to achieve a broader absorbance spectrum and improve photothermal effect. Beside using photothermal materials, lowering the enthalpy of evaporation using hydrogels that can absorb and retain water is another strategy to enhance solar evaporator performance. Polyvinyl alcohol (PVA) is a primary choice for interfacial solar evaporator due to its hydrophilicity and simple fabrication method. However, PVA has low absorption in the visible and nearinfrared regions. Therefore, the aim of this research is to develop carbon dot-based photothermal materials modified with PVA to produce high-performance and stable solar evaporators. In this study, carbon dots were synthesized from citric acid and urea using microwave heating in a relatively short time. The resulting carbon dots have a thermal conductivity of 0.05 W m-1 K -1 , significantly lower than that of CNT or graphene, which ranges from 3000 to 6000 W m-1 K -1 . Their absorbance capability extends into the visible light region, with a core structure rich in pyrrolic C-N bond configuration and numerous functional groups on the surface. These functional groups allow the formation of new energy states between the highest occupied molecular orbital (HOMO) state and the lowest unoccupied molecular orbital (LUMO), enhancing non-radiative relaxation and heat generation. The graphitic structure of the carbon dots synergizes with the pyrrolic configuration to boosts the photothermal effect, resulting in improved solar evaporation performance. The best absorbance and photothermal effect were achieved with a molar ratio of citric acid to urea of 1:3. Photothermal tests on the volumetric system showed an evaporation rate of 1.11 kg m?² h?¹ and an evaporation efficiency of 70%. The colloidal carbon dots were also stable in water, maintaining their absorbance and performance after 14 days, with a zeta potential of -40.6 mV. Carbon dots with the best absorbance and photothermal characteristics were composited with poly vinyl alcohol (PVA) and molded into films using a solutioncasting technique. The crosslinking process was carried out by adding citric acid as a crosslinking agent and heating at 140°C after synthesis. The resulting carbon dot/PVA hydrogel film has broad absorbance up to the near-infrared region, is hydrophilic (contact angle <60?), flexible, and exhibits excellent mechanical properties (tensile strength of 9 MPa, elongation at break of 257%, and elastic modulus of 7 MPa). With these characteristics, the carbon dot/PVA film produced evaporation rates of 1.58 kg m?² h?¹ at 1 kW m?² irradiation and 3.01 kg m?² h?¹ at 4 kW m?² irradiation in an interfacial solar evaporator system. This evaporation rate is six times higher than that of direct water heating at 1 kW m?² irradiation. The increase in evaporation rate is supported by the decrease in the enthalpy of evaporation from 2448.8 kJ kg?¹ for water at 22°C to 1827 kJ kg?¹ for the system using the carbon dot/PVA film. With this lower enthalpy value, the calculated evaporation efficiency of the carbon dot/PVA film is 80%. The film also demonstrated stable performance over nine reuses. Furthermore, performance tests using seawater and water contaminated with organic dyes proved that the carbon dot/PVA film-based solar evaporator is effective for desalination and wastewater purification.